Microbial Inoculants and Industrial Solid Wastes as Soil Amendments in Agroforestry - Aggarwal, Honey (My University, 2011)
Present study evaluated growth of Populus deltoides G48 and Toona ciliata over a period of six months, in nursery soil amended with 10% fly ash (v/v), 5% distillery waste (v/v), 20% farmyard manure (v/v) and microbial consortium of Pseudomonas striata and Azotobacter sp. @ 30 ml per pot in different combinations leading to twelve different treatments with 16 replicates in completely randomized block design. Biometric parameters such as plant height, collar diameter and total dry biomass were analyzed which indicated that the treatment (T8) comprising of fly ash @ 10% (v/v), farmyard manure @ 20% (v/v) and microbial consortium @ 30ml / pot promoted growth of P. deltoides. The results indicated that combined addition of fly ash, farm yard manure and microbial inoculants can be used as a good potting mixture for improving survival rates and plant growth in forestry nurseries.
Ph.D
Keywords: Populus deltoides; Toona ciliata; flyash; distillery waste; nursery trial; farmyard manure